The evaluation of nailfold capillaroscopy pattern in patients with fibromyalgia - İlke Coşkun Benlidayı,; Esra Kayacan Erdoğan,; Aylin Sarıyıldız, (Archives of Rheumatology, 2021)
Objectives: This study aims to evaluate nailfold capillaroscopic pattern in patents with fibromyalgia and to assess the relation of capillaroscopic parameters with clinical variables and disease-related measures. Patients and methods: This cross-sectional, case-control study included 60 participants (4 males, 56 females; mean age: 44.0±8.2 years; range, 26 to 64 years) between August 2019 and November 2019. All participants were divided into two groups as the primary fibromyalgia group (n=30) who met the 2016 modified American College of Rheumatology Diagnostic Criteria for Fibromyalgia and the control group (n=30) consisting of age- and sex-matched healthy individuals. Nailfold capillaroscopy was performed by a digital microscope under a magnification of 200X. Capillary density, capillary loop diameter, number of dilated, giant and neoangiogenic capillaries, capillary shape, number of avascular areas, micro-aneurysms and micro-hemorrhages were evaluated by an assessor who was blind to the group allocation. In the fibromyalgia group, Widespread Pain Index, Symptom Severity Scale scores, and Fibromyalgia Severity scores were calculated. Health status and presence of benign joint hypermobility syndrome (BJHS) were evaluated using the Fibromyalgia Impact Questionnaire (FIQ) and revised Brighton criteria, respectively. Results: Of the capillaroscopic parameters, the mean capillary loop diameter, number of micro-aneurysms, avascular areas, and neoangiogenic capillaries were significantly higher in the patient group compared to the controls (p<0.001, p=0.016, p=0.038, and p=0.04, respectively). Nailfold capillaroscopic findings did not significantly differ between the patients with (n=16) and without concomitant BJHS (n=14). Of the disease-related measures, only FIQ score showed a weak correlation with the number of dilated capillaries (p=0.324). Conclusion: Patients with fibromyalgia have distinct capillaroscopic patterns than healthy population. Capillaroscopic features, in general, are not related to clinical variables and disease-related measures.